COMMUNITY SERVICE THROUGH A READING ALOUD EVENT TO PROMOTE A READING-LOVING FAMILY - Kartiningsih, Rindrah; Mikail, Izzaditya Dharmaputra; Reku, Angelina Merici Wua; Dermawan, Zahwa Amelia Putri; Soenarko, Zahra Pramatatya; Pasopati, Rommel Utungga (Masyarakat: Jurnal Pengabdian, 2025)
The purpose of this service is to provide knowledge about Read Aloud skills. This community service approach includes introduction, service delivery, and evaluation. The approach in this report is documentation. This community empowerment is carried out through reading techniques by parents to their children to improve literacy. This activity has taken place successfully and was attended by approximately 30 parents and children from RT 5 RW 3 Peneleh Surabaya on May 27, 2025. In practice, parents read aloud short stories to their children. As a result, this community service plays a role via literacy in improving reading habits among families through the Read Aloud technique. This technique is also excellent for improving the relationship between parents and children through daily reading. In conclusion, this service is important to increase literacy, especially among families in RT 5 RW 3 Peneleh Surabaya, especially parents are motivated to read familiar reading together with their children. The implication of this service is how Reading Aloud fosters reading habits in families by involving parents and children in a closer bond.